Management of Sjogren’s Dry Eye Disease—Advances in Ocular Drug Delivery Offering a New Hope - Kevin Y. Wu; Wei T. Chen; Y-Kim Chu-Bédard; Gauri Patel; Simon D. Tran (Pharmaceutics, 2022)
Sjögren’s syndrome is a chronic and insidious autoimmune disease characterized by lymphocyte infiltration of exocrine glands. Patients typically present with dry eye, dry mouth, and other systemic manifestations. Currently, the available molecules and drug-delivery systems for the treatment of Sjögren’s syndrome dry eye (SSDE) have limited efficacy since they are not specific to SSDE but to dry eye disease (DED) in general. The current treatment modalities are based on a trial-and-error approach using primarily topical agents. However, this approach gives time for the vicious cycle of DED to develop which eventually causes permanent damage to the lacrimal functional unit. Thus, there is a need for more individualized, specific, and effective treatment modalities for SSDE. The purpose of this article is to describe the current conventional SSDE treatment modalities and to expose new advances in ocular drug delivery for treating SSDE. A literature review of the pre-clinical and clinical studies published between 2016 and 2022 was conducted. Our current understanding of SSDE pathophysiology combined with advances in ocular drug delivery and novel therapeutics will allow the translation of innovative molecular therapeutics from the bench to the bedside.